The Tax regime in the Constitution of the Republic of Ecuador - Torres-Rodas, Tiberio (DICERE Revista de Derecho y Estudios Internacionales, 2024)
This paper presents an analysis of the provisions of the Constitution of the Republic of Ecuador in force since 2008, which are related to the national tax system. It begins with a brief reference to the conception of the State in terms of the notion of good living and the civic obligation to contribute to the sustainability of public spending. The constitutional principles guiding the tax activity and the extrafiscal aspects of the tribute and the tax regime are then studied in consideration of the conception of the State as guarantor of rights. Finally, a very brief description of the exercise of the tax power of the State, in relation to the different types of taxes, is made.